2014
DOI: 10.1002/chem.201304861
|View full text |Cite
|
Sign up to set email alerts
|

Borylation of Unactivated Aryl Chlorides under Mild Conditions by Using Diisopropylaminoborane as a Borylating Reagent

Abstract: The synthesis of arylboronic ester derivatives from aryl chlorides by using aryl(amino)boranes is described. Palladium-catalyzed coupling between aryl chlorides and diisopropylaminoborane leads to the formation of a CB bond under mild conditions. A wide range of functional groups are tolerated, making this method particularly useful for the borylation of functionalized aromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Unfortunately, however, reactions under these optimized conditions using DPEPhos failed to promote the borylation of dibromide 3 b . Reoptimization of the reaction conditions showed that using KI together with CyJohnPhos, markedly improved the yield of 1 b , affording product 1 b in 97 % NMR yield (entry 2, see also the Supporting Information (SI) for details of optimization and some discussion regarding the effect of KI) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, however, reactions under these optimized conditions using DPEPhos failed to promote the borylation of dibromide 3 b . Reoptimization of the reaction conditions showed that using KI together with CyJohnPhos, markedly improved the yield of 1 b , affording product 1 b in 97 % NMR yield (entry 2, see also the Supporting Information (SI) for details of optimization and some discussion regarding the effect of KI) …”
Section: Methodsmentioning
confidence: 99%
“…This highlights the synthetic advantage of our protocol over previously reported methods using organolithium reagents . In particular, the tolerance of an aryl chloride moiety, as shown for 1 k , is notable when considering that the report that the borylation of aryl chlorides occurs with 4 a using a Pd/XPhos catalyst . Our protocol also allowed the synthesis of π‐extended analogue 1 p as well as diarylborinic acids containing nitrogen ( 1 q ) and sulfur ( 1 r ) tethers.…”
Section: Methodsmentioning
confidence: 99%
“…The transition metal‐catalyzed C−X (X=Cl, Br, I, OTf) borylation reaction provides another option for introducing boronate ester groups selectively into fluorinated aryl halides or triflates [60–70] . Masuda et al .…”
Section: Synthesis Of Fluorinated Aryl Boronatesmentioning
confidence: 99%
“…Several examples of transition metal‐catalyzed C−X borylation reactions generating products with the C−B moiety located ortho , meta , and para to the fluorine substituents have been reported [58,63–67,69] . For example, in 2014, Pucheault et al .…”
Section: Synthesis Of Fluorinated Aryl Boronatesmentioning
confidence: 99%
“…The typical borylation setup makes use of aryl/hetaryl halides, borylation reagents, and transition metal catalysts. Both iodide and chloride are able to couple with either pinB-Bdan [49] or diisopropylaminoborane [50] under palladium catalysis conditions (Table 1, entries 1 and 2). The isolated yields of indolylboronates ranged from 47−85%.…”
Section: Synthetic Approaches To Indolylboronic Acidsmentioning
confidence: 99%